2005
DOI: 10.1038/sj.ejhg.5201478
|View full text |Cite
|
Sign up to set email alerts
|

Mutation spectrum leading to an attenuated phenotype in dystrophinopathies

Abstract: Although Becker muscular dystrophy (BMD; MIM 300376) is mainly caused by gross deletions of the dystrophin gene, the nature of the mutations involved in the remaining cases is of importance because of the milder clinical course of Becker. We have extensively characterized the mRNA changes associated with five novel point mutations giving rise to a Becker phenotype, which confirm that Becker arises largely due to alterations in splicing. In two cases the milder phenotype arises because of exon skipping, leading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 35 publications
0
22
0
1
Order By: Relevance
“…2A). The use of alternative cryptic splice sites could possibly lead to frame-restoring transcripts, resulting in a mixture of aberrantly and correctly spliced transcripts [Lohmann and Gallie, 2004;Tuffery-Giraud et al, 2005], which may explain the reduced disease severity observed; however, why this would be the case in some family members and not in others, remains unclear.…”
Section: Discussionmentioning
confidence: 90%
“…2A). The use of alternative cryptic splice sites could possibly lead to frame-restoring transcripts, resulting in a mixture of aberrantly and correctly spliced transcripts [Lohmann and Gallie, 2004;Tuffery-Giraud et al, 2005], which may explain the reduced disease severity observed; however, why this would be the case in some family members and not in others, remains unclear.…”
Section: Discussionmentioning
confidence: 90%
“…Although insufficient tissue was available from the clinical biopsy for qRT-PCR studies, mRNA sequencing showed no evidence of significant amounts of a second mRNA species, such as may be seen with stop codon-encoding point mutations that induce exon skipping via alteration of ESE elements. 24 This raises the possibility that the premature stop codon signal may be subject to ribosomal readthrough, which is sequence context dependent. 25 However, readthrough does not appear to correlate well with phenotype in DMD patients, 26 and in only a single case has readthrough been implicated in ameliorating a disease phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…27 Another group of patients has less than 20% dystrophin expression and they display intermediate phenotype. 3,6,9,26 The mechanism(s) underlying the reduced clinical severity in these patients are not completely understood. Several hypotheses have been suggested including epigenetic, nutritional, and environmental factors, and a palliative effect of low-level dystrophin expression.…”
Section: Discussionmentioning
confidence: 99%